Novel compound heterozygous mutations in UHRF1 are associated with atypical immunodeficiency, centromeric instability and facial anomalies syndrome with distinctive genome-wide DNA hypomethylation. Issue 9 (2nd December 2022) - Unoki, Motoko; Velasco, Guillaume; Kori, Satomi; Arita, Kyohei; Daigaku, Yasukazu; Yeung, Wan Kin Au; Fujimoto, Akihiro; Ohashi, Hirofumi; Kubota, Takeo; Miyake, Kunio; Sasaki, Hiroyuki
Abstract: Immunodeficiency, centromeric instability and facial anomalies (ICF) syndrome is in most cases caused by mutations in either DNA methyltransferase ( DNMT ) 3B, zinc finger and BTB domain containing 24, cell division cycle associated 7 or helicase lymphoid-specific . However, the causative genes of a few ICF patients remain unknown. We, herein, identified ubiquitin-like with plant homeodomain and really interesting new gene finger domains 1 ( UHRF1 ) as a novel causative gene of one such patient with atypical symptoms. This patient is a compound heterozygote for two previously unreported mutations in UHRF1 : c.886C > T (p.R296W) and c.1852C > T (p.R618X). The R618X mutation plausibly caused nonsense-mediated decay, while the R296W mutation changed the higher order structure of UHRF1, which is indispensable for the maintenance of CG methylation along with DNMT1. Genome-wide methylation analysis revealed that the patient had a centromeric/pericentromeric hypomethylation, which is the main ICF signature, but also had a distinctive hypomethylation pattern compared to patients with the other ICF syndrome subtypes. Structural and biochemical analyses revealed that the R296W mutation disrupted the protein conformation and strengthened the binding affinity of UHRF1 with its partner LIG1 and reduced ubiquitylation activity of UHRF1 towards its ubiquitylation substrates, histone H3 and proliferating cell nuclear antigen -associated factor 15 (PAF15). We confirmed that the R296W mutation causes hypomethylation at pericentromeric repeats by generating the HEK293 cell lines that mimic the patient's UHRF1 molecular context. Since proper interactions of the UHRF1 with LIG1, PAF15 and histone H3 are essential for the maintenance of CG methylation, the mutation could disturb the maintenance process. Evidence for the importance of the UHRF1 conformation for CG methylation in humans is, herein, provided for the first time and deepens our understanding of its role in regulation of CG methylation. Graphical Abstract: Ubiquitin-like with plant homeodomain (PHD) and really interesting new gene (RING) finger domains 1 is composed of five domains: an ubiquitin like domain, a tandem Tudor domain, a PHD, an SET and RING-associated domain and a RING domain. Locations of the R618X and R296W mutations found in an 'ICF type X' patient are indicated in bold. The R618X mutation plausibly causes nonsense-mediated decay, while the R296W mutation changes the binding stoichiometry with histone H3, strengthens the binding affinity to LIG1 and decreases ubiquitylation activity towards histone H3 and PAF15. These changes could disturb the process of maintenance of CG methylation and possibly also affect the de novo CG methylation, resulting in distinctive CG hypomethylation pattern in the patient.